Selective Conventional Approach for Management of Bleeding Uterine Arteriovenous Malformation: A Case Report - Jyoti Dahal; Suman Raj Tamrakar; Rupesh Singh Basnyat (Journal of Nepal Medical Association)
Uterine Arteriovenous malformation is an abnormal connection between artery and veins in the uterus. Although rare, it is an important cause of abnormal uterine bleeding in women and can lead to life threatening torrential hemorrhage. Traditionally such cases have been managed with medical therapy and hysterectomy. However, selective uterine artery embolization and hysteroscopy guided procedures are the treatment of choices. We hereby report a case of 25 years lady who presented with irregular heavy vaginal bleeding and diagnosed to have uterine arteriovenous malformation by magnetic resonance imaging. She was managed conventionally with condom tamponade during bleeding due to intrauterine procedure and later with hormonal therapy. The patient later had regular cycles avoiding hysterectomy at a young age. The objective of this case report is to share the successful application of uterine balloon tamponade (UBT) for the active management of bleeding uterine arteriovenous malformation which has not been reported so far which can be applied especially in a resource limited setup.